Determinants of final infarct size and incidence of aborted infarction in patients treated with primary coronary intervention and adjunctive abciximab therapy - Sciagrà, R.; Parodi, G.; Sotgia, B.; Antoniucci, D.; Pupi, A. (Nuklearmedizin - NuclearMedicine, 2008)
Aims: Assess the determinants of final infarct size in patients successfully treated with primary percutaneous coronary intervention (PCI) and abciximab therapy and check whether infarct abortion may occur. Patients, methods: In 208 patients we examined the parameters that predict final infarct size and the incidence of aborted infarction, defined by completely normal perfusion and regional wall motion plus > 50% left ventricular ejection fraction (LVEF) in gated single-photon emission computed tomography (SPECT) acquired at one month. Results: In linear regression analysis, sex (p < 0.0001), high cholesterol (p < 0.05), Killip class (p < 0.0001), symptom-to-reperfusion time (p < 0.001), admission ST segment elevation (p < 0.0001), infarct related artery (p < 0.05), and pre-procedural TIMI flow (p < 0.002) were significant univariate predictors of final infarct size. In multiple linear regression analysis, symptom-to-reperfusion time (p < 0.001), Killip class (p < 0.0001), ST segment elevation (p < 0.003), and sex (p < 0.03) remained significant predictors, model R2 = 0.53. Aborted infarction was registered in 32 patients, more frequently female (59% versus 21%, p < 0.00001), older (p < 0.02), with larger prevalence of TIMI grade 3 (p < 0.05) and lower ST segment elevation at admission (p < 0.05). Conclusions: Sex, reperfusion delay, and initial infarct severity as indicated by Killip class and/or ST segment elevation appear the determinants of final infarct size in patients treated with primary PCI. The presence of aborted infarction seems related to the same factors and to preserved TIMI 3 flow.
Keywords: Acute myocardial infarction; gated single-photon emission computed tomography; myocardial perfusion scintigraphy; percutaneous coronary intervention